Concurrent Occurrence of Obsessive-Compulsive Disorder and Myofascial Pain Dysfunction Syndrome: A Case Series - Sara Pourshahidi; Hooman Ebrahimi; Younes Ghoreyshi; Nafiseh Sheykhbahaei (Frontiers in Dentistry)
Objectives: Myofascial pain dysfunction syndrome (MPDS) is a musculoskeletal disorder with a multifactorial etiology. Some investigations suggest psychological disorders as a major risk factor for MPDS. This study is the first case series to report patients with obsessive-compulsive disorder (OCD) and MPDS comorbidity.